Construction of functional soybean peptide–cyclodextrin carboxylate nanoparticles and their interaction with porcine pancreatic α-amylase. (December 2022) - Liu, Yuwan; Li, Xiaojing; Sang, Shangyuan; Julian McClements, David; Chen, Long; Long, Jie; Jiao, Aiquan; Wang, Jinpeng; Xu, Xueming; Jin, Zhengyu; Qiu, Chao
Graphical abstract: Highlights: A novel soybean polypeptide composite NPs were prepared based on hydrogen bonding. Particle size of the SPT-SACD NPs were greatly influenced by the SPT/SACD mass ratio. Van der Waals forces and hydrogen bonds are the main driving force for interactions. The SPT-SACD NPs quenched α-amylase intrinsic fluorescence. The SPT-SACD NPs enhanced the inhibitory effect of EGCG on α-amylase activity. Abstract: In this study, soybean peptide-succinic acid-modified cyclodextrin (SPT-SACD) nanoparticles (NPs) were successfully fabricated by combining SPT and SACD using an antisolvent precipitation approach. The effects of the average molecular weight of SPT and the SPT/SACD mass ratio on the structure and properties of the SACD-SPT NPs were investigated. Under optimal conditions, the SPT/SACD mass ratio was 2:1, and the SPT average molecular weight was 300 Da. SPT-SACD NPs were prepared under these conditions were spherical and had good uniformity. The particle sizes by DLS of SPT1 (300 Da) /SACD and SPT2 (500 Da) /SACD were in the range of 250–400 nm. The interaction between α-amylase and SPT-SACD NPs was investigated using ultraviolet visible (UV–Vis) absorption, fluorescence, and circular dichroism (CD) spectroscopy. The results of the fluorescence spectra and CD spectroscopy suggested that the presence of SPT-SACD NPs changed the microenvironment of the aromatic amino acid residues, which leads to the change of enzyme protein structure. The SPT-SACD NPs statically quenched the intrinsic fluorescence of the α-amylase by forming a complex with the enzyme. Moreover, the SPT-SACD NPs significantly improved the inhibitory effect of EGCG on α-amylase. The semi-inhibitory concentration (IC50 ) decreased from 0.324 to 0.248 mg/mL. This study provides an improved understanding of the interaction mechanism between polypeptide-cyclodextrin complexes and digestive enzymes, which may facilitate the design of functional foods.